CCAFS research informs several gender and agriculture submissions of the Africa Group of Negotiators (AGN) to the United Nations Framework Convention on Climate Change (UNFCCC) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
CCAFS facilitated and contributed text to the Africa Group of Negotiators (AGN) submission on the UNFCCC Gender Action Plan at the 46th Subsidiary Body for Implementation (SBI46) in May 2017 and country submissions from Ghana and Kenya; support was provided to the AGN Expert Support (AGNES) gender facilitator at the Gender Action Plan negotiations at COP25; technical support and text provided in the AGNES submission on Good Practices in Gender Mainstreaming of National Adaptation Plans and Nationally Determined Contributions (NDCs).